Designing robotic cabinets that assist users’ tidying behaviors - Lee, Han byeol; Kang, Dahyun; Kwak, Sonya S.; Choi, Jong Suk (2020 29TH IEEE INTERNATIONAL CONFERENCE ON ROBOT AND HUMAN INTERACTIVE COMMUNICATION (RO-MAN), 2020)
With the development of robotic technology, various types of robotic products have been developed, ranging from robotic objects that support small daily necessities (such as robotic umbrellas and frames) to robotic furniture (such as robotic chairs and drawers). Owing to consumerism, the consumer marketplace now overflows with surplus products, and storage and organizational products have been increasingly necessary. With this social stream, we focused on designing robotic storage furniture in this study. To create such a type of furniture that is acceptable by consumers, a qualitative user study was conducted with 16 subjects by analyzing the users' behaviors when using ordinary storage furniture. From this user study, we found strong user needs in terms of organizing and finding objects. Thus, we developed two types of robotic cabinets: the first one to assist users' organizing behavior and the second one to assist their finding behavior. To examine the effectiveness of the developed prototypes, we executed a 3 (behavior the robotic cabinet assists: baseline vs. organizing vs. finding) within-participants experiment. The result shows that significant effects vary depending on the type of robotic cabinet.